Additional improvement in regional myocardial ischemia after intracardiac injection of bone marrow cells during CABG surgery - Gowdak, Luís Henrique Wolff; Schettert, Isolmar Tadeu; Rochitte, Carlos Eduardo; de Carvalho, Leonardo P.; Vieira, Marcelo Luiz Campos; Dallan, Luís Alberto Oliveira; de Oliveira, Sérgio Almeida; César, Luiz Antonio Machado; Brito, José Oscar Reis; Guarita-Souza, Luiz César; de Carvalho, Antonio Carlos Campos; Krieger, Jose Eduardo (Frontiers in Cardiovascular Medicine, 2023)
Background Post-procedure residual ischemia is associated with worse prognosis in patients with coronary artery diasease (CAD). Objective We evaluated whether autologous bone marrow-derived cells (BMC) contribute to additional reduction in regional stress-induced myocardial ischemia (SIMI) in patients undergoing incomplete coronary artery bypass graft surgery (CABG). Methods In a double-blind, randomized, placebo-controlled trial, we enrolled 143 patients (82% men, 58 ± 11 years) with stable CAD and not candidates for complete CABG. They received 100 million BMC (n = 77) or placebo (n = 66) injected into ischemic non-revascularized segments during CABG. The primary outcome was improvement on SIMI quantified as the area at risk in injected segments assessed by cardiovascular magnetic resonance (CMR) 1, 6, and 12 months after CABG. Results The reduction in global SIMI after CABG was comparable (p = 0.491) in both groups indicating sustained beneficial effects of the surgical procedure over 12 month period. In contrast, we observed additional improvement in regional SIMI in BMC treated group (p = 0.047). Baseline regional SIMI values were comparable [18.5 (16.2–21.0) vs. 18.5 (16.5–20.7)] and reached the lowest values at 1 month [9.74 (8.25; 11.49) vs. 12.69 (10.84; 14.85)] for BMC and placebo groups, respectively. The ischemia’s improvement from baseline represented a 50% difference in regional SIMI in favor of the BMC transplanted group at 30 days. We found no differences in clinical and LVEF% between groups during the 12 month follow-up period. The 1 month rate of major adverse cerebral and cardiovascular events (MACCE) (p = 0.34) and all-cause mortality (p = 0.08) did not differ between groups 1 month post intervention. Conclusion We provided evidence that BMC leads to additional reduction in regional SIMI in chronic ischemic patients when injected in segments not subjected to direct surgical revascularization. This adjuvant therapy deserves further assessment in patients with advanced CAD especially in those with microcirculation dysfunction. Clinical trial registration https://clinicaltrials.gov/, identifier NCT01727063